2014
DOI: 10.5750/ejpch.v2i4.833
|View full text |Cite
|
Sign up to set email alerts
|

Physician smoking cessation counseling and adherence to the Clinical Practice Guideline

Abstract: Objective The U.S. Public Health Service Clinical Practice Guideline recommends that physicians provide tobacco cessation interventions to their patients at every visit. While many studies have examined the extent to which physicians implement the guideline's “5 A's”, few studies have examined the extent to which physicians implement the guideline's “5 R's” which are to be used in a Motivational Interviewing (MI) consistent style with smokers not ready to quit. This study examined the extent to which physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Participants were also from a single academic safety-net hospital so the views offered may not generalize to doctors in settings. Finally, doctor reports of their behaviour may not correspond with their actual behaviour; however, their descriptions were consistent with our prior observational study of their counselling efforts [17].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Participants were also from a single academic safety-net hospital so the views offered may not generalize to doctors in settings. Finally, doctor reports of their behaviour may not correspond with their actual behaviour; however, their descriptions were consistent with our prior observational study of their counselling efforts [17].…”
Section: Discussionsupporting
confidence: 73%
“…Results clearly indicate that patients are unlikely to receive highquality, evidence-based counselling for smoking cessation despite doctors generally believing in its importance. Although recent changes have required medical schools to include basic patientprovider communication skills in their curricula [26,30], most practising doctors have not received this training [17,31]. Only three doctors (21%) who participated in this study reported having formal training on smoking cessation counselling.…”
Section: Practice Implicationsmentioning
confidence: 95%
“…Since at least 70% of smokers visit their physician annually, clinical encounters present an opportunity to assess e‐cigarette use among smokers and provide them with evidence‐based information about e‐cigarettes, in addition to following clinical practice guidelines for treating tobacco use and dependence . A large body of research has assessed physician compliance with the US Public Health Service (USPHS) tobacco cessation clinical practice guidelines and approaches to smoking cessation counselling more generally; however, research on physicians' approaches to discussing e‐cigarettes with their patients is limited. Indeed, the USPHS provides clinical practice guidelines for treating tobacco use and dependence, but it does not include guidelines on providing information about e‐cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical guideline emphasized the importance of referring smokers in general to a specially trained physician. 24 Research into patients' perceptions of doctors' advice to quit smoking revealed why some patients had not been counseled by their physician, and the fact that physicians feel that there is not enough time during their shifts to have this conversation about cessation. A criticism of this inference is that it takes only a few minutes to provide this advice.…”
mentioning
confidence: 99%